Visual Outcome and Complications of Boston Keratoprosthesis: An Experience from North West Pakistan - Hussain, Ibrar (Pakistan Journal of Ophthalmology, 2017)
Purpose: The Purpose of this study is to document the visual outcome and complications of Boston Keratoprosthesis implant in corneal blindness. Study Design: Descriptive case series. Place & Duration of Study: This study was performed at Khyber Teaching Hospital Peshawar from April 2009 to April 2016. Material & Method: Nine eyes of 8 patients were included in the study. In all eyes preoperative visual acuity recorded and slit lamp examination performed. In each case status of anterior segment and diagnosis documented, B-scan performed and Boston keratoprosthesis implanted under general anesthesia. Postoperative visual acuity and complications documented during the course of follow up and data analyzed. Results: Preoperative diagnoses of these patients include Steven Johnson Syndrome in 3 (33.3%) eyes, bomb blast injury in 3 (33.3%) eyes, healed corneal ulcers with failed corneal graft in 2 (22.2%) eyes and Peter anomaly in 1 (11.1%) eye. All the corneas were opaque and vascularized and preoperative visual acuity was perception of light only. In final fallow up visual acuity was 20/200 in 2 (22.2%), 10/200 in 2 (44.4%), 3/200 in 1 (11.1%), perception of light in 3 (33.3%) and no perception of light in 1 (11.1%). Postoperative complications were retro-prosthetic membrane in 6(66.6%) eyes, glaucoma in 1 (11.1%) eye, device extrusion in 3 (33.3%), sterile keratolysis in 3 (33.3%), phthisis bulbi in 3 (33.3%), retinal detachment in 1 (11.1%) and endophthalmitis in 1 (11.1%) eye. Conclusion: Type 1 Boston Keratoprosthesis implant still has poor prognosis in patients with SJS and severely traumatized eye e.g., bomb blast injuries and this is related mainly to preexisting bad eye condition. Key Words: Artificial cornea, Boston Keratoprosthesis, Corneal blindness.